Extra income is peanuts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Dried, roasted or processed into peanut butter, peanuts mean money for millions of households. World peanut production is around 30 million tonnes, with China, USA, Argentina and India as major export producers. In Africa, the largest producers are...